Dismantling the myth of the growth-inequality trade-off - Mario Negre; José Cuesta; Ana Revenga; Prescott J. Morley (Deutsches Institut für Entwicklungspolitik (DIE), 2019)
Conventional economic wisdom has long maintained that there is a necessary trade-off between pursuit of the efficiency of a system and any attempts to improve equity between participants within that system. Economist Robert Lucas demonstrated the implications of this common economic axiom when he wrote: “Of the tendencies that are harmful to sound economics, the most seductive, and in my opinion the most poisonous, is to focus on questions of distribution [...] the potential for improving the lives of poor people by finding different ways of distributing current production is nothing compared to the apparently limitless potential of increasing production.” (Lucas, 2004) Indeed, many economists have suggested that too little inequality or too generous a distribution of benefits may undermine the individual's incentive to work hard and take risks. Setting aside the harsh rhetoric used by Lucas, the practical and ethical acceptability of such a trade-off is debatable. Moreover, evidence from recent decades suggests that the trade-off itself is, in many cases, entirely avoidable. A large body of research has shown that improved competition and economic efficiency are indeed compatible with government efforts to address inequality and reduce poverty, as assessed in a World Bank report (World Bank, 2016). Contrary to another common belief about economic interventions, this research indicates that such policy interventions can be tailored to succeed in all countries and at all times; even low- and middle-income countries in times of economic crisis can successfully pursue policies to improve economic distribution, with negligible negative impacts on efficiency and, in many cases, even positive ones. Some examples of such pro-equity and pro-efficiency measures include those promoting early childhood development, universal health care, quality education, conditional cash transfers, rural infra-structure investment, and well-designed tax policy. Overall, four critical policy points stand out: A trade-off is not inevitable. Policymakers do not need to give up on reducing inequality for the sake of growth. A good choice of policies can achieve both. In the last two decades, research has generated substantive evidence about which policies work to foster growth and reduce inequalities. Policies can redress the inequalities children are born into while fostering growth. But the wrong sets of policies can magnify inequalities early in life and thereafter. All countries can, under most circumstances, implement policies that are both pro-equity and pro-efficiency.
Keywords: 330; Agenda 2030; Armut und Ungleichheit